(untitled) (Pedagogy of Higher and Secondary Education, 2004)
The article reveals the necessity of personality-oriented teaching at the practical lessons of the English language at the Pedagogical University. Great attention is focused on the changing of the teacher’s role in the process of personality-oriented teaching.